Beautiful Losers - Rose, Aaron; Leonard, Joshua; Yelland, Tobin (Revolver Entertainment, 2009)
In "Beautiful Losers", Aaron Rose and Joshua Leonard's energized documentary celebrates the do-it-yourself subculture of artists engulfed in skateboarding, graffiti, and punk who gravitated toward the Lower East Side Alleged Gallery (of which Rose was the curator) in the late '80s. Here a motley collection of geeks, oddballs, lunatics, and downtowners - including Shepard Fairey, Margaret Kigallen, Mike Mills, Barry McGee, Jo Jackson, Chris Johanson, Harmony Korine, Stephen Powers, Geoff McFeteridge, Thomas Campbell, and Ed Templeton - recreated the cooperative spirits of Renoir with unfettered innocence, a lack of pretentiousness, and childlike glee, slapping together their artworks like Chuck Jones characters in heat. As one artist remarks in the film, they were just a 'bunch of dumb, bored kids. All you had to do was have heart.' Or as Stephen Powers comments, 'It's really bad. I love it!' ... It is a rare experience indeed that an art documentary comes along that is not self-serving, self-important, and/or depressing. "Beautiful Losers" is a film that is infused with cool, invigorating life and with the bountiful joy and blessed-out abandon of artistic creation. [www.filmcritic.com]